2018
DOI: 10.1038/s41598-018-32406-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of parity on rat mammary carcinogenesis after pre- or post-pubertal exposure to radiation

Abstract: Radiation exposure during the peri-pubertal period is a proven risk factor for breast cancer, whereas parity is an established protective factor. The present study investigated whether parity imposes differential protective effects against radiation-induced rat mammary carcinoma depending on the age at exposure. Pre- and post-pubertal female rats, irradiated or left unirradiated, were mated and allowed to nurse until weaning or left unmated. Appearance of mammary tumors was monitored, and serum concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
(80 reference statements)
4
12
0
Order By: Relevance
“…Notably, the subtype of breast cancer is influenced by various factors such as the number of births and obesity, and differences in these reproductive and lifestyle factors might underlie the inconsistency among the reported results (23). On the other hand, rats mainly develop hormone receptor-positive mammary carcinomas in both spontaneous and chemical-induced models (6,17). Our present data concerning subtype frequency are consistent with published data (17).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Notably, the subtype of breast cancer is influenced by various factors such as the number of births and obesity, and differences in these reproductive and lifestyle factors might underlie the inconsistency among the reported results (23). On the other hand, rats mainly develop hormone receptor-positive mammary carcinomas in both spontaneous and chemical-induced models (6,17). Our present data concerning subtype frequency are consistent with published data (17).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, rats mainly develop hormone receptor-positive mammary carcinomas in both spontaneous and chemical-induced models (6,17). Our present data concerning subtype frequency are consistent with published data (17).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, young adult (7-week-old) male mice were used in the present study. It has been reported that biological radiation effects vary with age and sex 36,37 . Further studies should examine whether age and sex affect radiation-induced antioxidant changes.…”
Section: Discussionmentioning
confidence: 99%